MANAJEMEN PROGRAM KELOMPOK KERJA GURU (KKG) DALAM MENINGKATKAN KOMPETENSI PEDAGOGIK GURU SD - tatang, tatang (Wali Pikir: Journal Of Education, 2023)
This research has a background in teacher quality problems that continue to be highlighted and its professionalism continues to be questioned by various elements. This study also aims to analyze and know more in depth about the management of the teacher working group (KKG) in improving the pedagogic competence of elementary school teachers in the Giriharja school cluster and the Manggahang school cluster Baleendah Subdistrict, Bandung Regency. The research method and procedure is to use a case study method with a qualitative approach, through data collection with interviews, to school principals, KKG administrators and teachers, documentation and observation studies during the KKG activities. The results and conclusions of this study are: (1) planning is prepared jointly by KKG management, teachers, principals and school supervisors by capturing input from parties related to school cluster activities, followed by group discussions to provide teachers with flexibility in determining needs the profession. (2) organizing is done by forming the management structure of KKKS and KKG, and then dividing the tasks and functions of each structure. (3) the implementation of the KKG program is adjusted to the program plans that have been prepared previously. (4) Evaluation is carried out when and after the program is implemented. Research Implications are: Management of the Teacher Working Group Program (KKG) runs according to the management function, but there are strengths, weaknesses, opportunities, and challenges that need to be addressed by all parties so that the role of the GFC can improve teacher competency, especially pedagogic competence